Development of skin diseases following systemic exposure: example of dioxins - Sorg, Olivier; Saurat, Jean-Hilaire (Frontiers in Toxicology, 2023)
Most skin manifestations of exposure to toxic compounds are a consequence of a direct contact with the toxicants. However, some toxicants may reach the skin following systemic exposure, and promote skin diseases. Good examples of such chemicals are dioxin-like compounds. This family of lipophilic molecules comprises polychlorinated [dibenzodioxins, dibenzofurans and biphenyls]. The most potent member of this family is 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Following oral ingestion of as little as a few mg TCDD, skin lesions appear in a couple of weeks, starting from the face and diffuse then on the trunk and limbs. This syndrome was historically called "chloracne" and the skin lesions have now been shown to be skin hamartoma induced by TCDD. Sweat glands release their lipid content on the surface of the skin by a holocrine secretion, and so any lost sebocyte should be transmitted to progenitor cells to differentiate and migrate to the sebaceous gland to replace the lost sebocyte. TCDD acts by inducing a switch in this signal and skin hamartoma develop in place of new sebocytes.